Reverse supply chain service process model for the iron and steel industry - WANG Lei; XIA Xu-hui; XIONG Ying-qing; LIU Jun-wei; ZHOU Min (工程科学学报)
The basic definition and the characteristics of three service principals of reverse supply chain service for the iron and steel industry is analyzed according to the reverse supply chain process of the iron and steel industry. Based on this work, a two-hierarchical and three-dimensional reverse supply chain service process model is built for the iron and steel industry. A three-dimensional service space is constructed, including services abstraction, service organization and collaborative operation, and service network control and service value-added. In the space, the first hierarchical service response constituted by the three stages of service programme matching and decision-making, and the second hierarchical service response constituted by the two stages of service function realization are accomplished. The key technology of service process realization including service modularization, service knowledge acquisition and sharing, and service modular intelligent matching is discussed. Finally, the feasibility of the model is proved by a case of scrap steel reverse supply service for one iron and steel enterprise.